HUBUNGAN ANTARA KEJADIAN POSTPARTUM BLUES TERHADAP PRODUKSI ASI IBU DENGAN ANAK YANG DI RAWAT DI PERINATOLOGI - Widia " Mona; Oswati " Hasanah; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Postpartum blues is a mental disorder as a result of women’s failure to adjust  their role after childbearing. The purpose of this study was to determine the relationship between the incidence of postpartum blues and mother’s milk production whose children admitted to perinatology room at ArifinAchmad hospital. The study design was analytic involving 33 respondents. The sampling method was accidental sampling. The analysis used is univariate and bivariate. Results showed that the majority of respondents are in early adulthood (26-35 years) (51,5%) and most of the labor wasmultipara (45,5%),respondents had post partum blues (27,3%) and most of the milk production are 5 cc (15,2%) and 20 cc(15,2%). Based on the statistical mannwhitney test, p value= 0,095, p value> 0,05, it can be concluded that there was nocorrelation between the incidence of postpartum blues andmother’s milk production whose children admitted to perinatology room. The results of this study recommend the nurse to perform health education about the effect of post partum blues after childbearing. Keywords: perinatology, post-partum blues, milk production.